Evaluation of the ELISA-F29 Test as an early marker of therapeutic efficacy in adults with chronic Chagas disease - Fabbro, Diana Lucrecia (2013)
This work compared the time at which negative seroconversion was detected by conventional serology (CS) and by the ELISA-F29 test on a cohort of chronic chagasic patients treated with nifurtimox or benznidazole. A retrospective study was performed using preserved serum from 66 asymptomatic chagasic adults under clinical supervision, and bi-annual serological examinations over a mean follow-up of 23 years. Twenty nine patients received trypanocide treatment and 37 remained untreated. The ELISA-F29 test used a recombinant antigen which was obtained by expressing the Trypanosoma cruzi flagellar calcium-binding protein gene in Escherichia coli. Among the untreated patients, 36 maintained CS titers. One patient showed a doubtful serology in some check-ups. ELISA-F29 showed constant reactivity in 35 out of 37 patients and was negative for the patient with fluctuating CS. The treated patients were divided into three groups according to the CS titers: in 13 they became negative; in 12 they decreased and in four they remained unchanged. ELISA-F29 was negative for the first two groups. The time at which negativization was detected was significantly lower for the ELISA-F29 test than for CS, 14.5 ± 5.7 and 22 ± 4.9 years respectively. Negative seroconversion was observed in treated patients only. The results obtained confirm that the ELISA-F29 test is useful as an early indicator of negative seroconversion in treated chronic patients.